Upaya Meningkatkan Motorik Halus Melalui Origami pada Anak Usia Dini di TK Al-Hikmah - Parapat, Asmidar (Prodi PIAUD STAI Sumatera Medan, 2021)
This study aims to improve fine motor skills through origami in early childhood at Al-Hikmah Kindergarten. The research method used was collaborative classroom action research using the model of Kemmis and Mc Taggart. The subjects of the study were 24 children of Group A consisting of 10 boys and 14 girls. The object of this research is fine motorskills. Data collection methods used were observation, documentation, and interviews. The instruments used were observation guidelines and interview guidelines. The data were analyzed using descriptive quantitative and qualitative techniques. The success indicator determined is if at least 75% of the 19 children have fine motor skills with good criteria. This research was conducted in three cycles. The results showed that the children's fine motor skills improved after the action through origami. The steps taken to improve children's fine motor skills are 1) the teacher explains how to fold paper using the demonstration method; 2) the child is given reinforcement with the word